If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying g(x) = 7x + -14 Multiply g * x gx = 7x + -14 Reorder the terms: gx = -14 + 7x Solving gx = -14 + 7x Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Divide each side by 'x'. g = -14x-1 + 7 Simplifying g = -14x-1 + 7 Reorder the terms: g = 7 + -14x-1
| 6+7y=48 | | .8333333333+.2x=.666666667 | | 13+11x=68 | | 2x+9x=11x | | 6x^2-16x+7=0 | | -4.3=0.7-5y | | 6x-2=3(x+1)+1 | | 4x-90=-6x+40 | | 4n^2-17n+4= | | 2d-7=11d+26 | | 8x+16=9x+9 | | C(m)=0.15m+0.95 | | 6y-4=y+6 | | 4(3x-2)=2(6x+9) | | P-17=67 | | X+-5x+3=-5 | | .16(x-36)=.83 | | 7x-4x=4x-2 | | 10+3j=31 | | 2.3y+1.2=2.12whatisy | | 4x(2x-1)(3x-5)=0 | | 7x+9-2x=11-12x-13 | | (x-4)(3x+8)=0 | | 8n-8=32 | | 3x+12-5x=19-15x+13x-7 | | 8x+15=19whatisx | | x^2+12y+36=10 | | 0-7x=7 | | 4x^4-25x^2+36=0 | | 15n^2-27n-6= | | x(x-8)=33 | | 7w=49 |